A single-atom dispersed heterostructure catalyst and a preparation method and application thereof

CN117947450BActive Publication Date: 2026-10-27CITY UNIVERSITY OF HONG KONG SHENZHEN FUTIAN RESEARCH INSTITUTE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211276014.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2026-10-27
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

然而,MOFs/COFs的合成和纯化以及后续的金属离子吸附过程是一个非常耗时的过程

Benefits of technology

[0035]1.本发明提供了一种单原子分散的异质结构催化剂,其可以用于电解水制氢、燃料电池、空气电池等。具体的,可以催化析氢反应,或者可以作为燃料电池或空气电池中的电极材料起催化电极反应的作用。具有催化活性高,过电势小,稳定性好等诸多优点,在能源转化领域有非常好的应用前景,例如,其中的电解水制氢技术在解决目前碳中和的目标中就扮演着非常重要的角色。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117947450B_ABST
    Figure CN117947450B_ABST
Patent Text Reader

Abstract

The application provides a single-atom dispersed heterostructure catalyst and a preparation method and application thereof, the catalyst comprising a heterostructure and a metal dispersed in the heterostructure in a single-atom form, and the heterostructure being a heterostructure composed of several oxides and / or several phosphides of high-valence metals. The catalyst is prepared by using a mineral gel, and the preparation method is rapid, simple, safe and feasible. Specifically, the solution mixing and standing process for preparing a precursor is a low-cost and large-scale application production method. The catalyst can be used in water electrolysis hydrogen production, fuel cells, air cells and the like, has the advantages of high catalytic activity, small overpotential, good stability and the like, and has a very good application prospect in the field of energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst and its preparation technology, and relates to a catalyst, its preparation method and application, specifically to a single-atom dispersed heterostructure catalyst and a method for preparing the catalyst using mineral gel, and the application of the catalyst in water electrolysis for hydrogen production, fuel cells, and air batteries. Background Technology

[0002] Hydrogen is an attractive energy source due to its high energy density and low pollutant emissions when burned in air. Among various hydrogen production methods, the electrochemical hydrogen evolution reaction (EER) is popular due to its simplicity and economy. However, the high cost of currently available commercial noble metal EER catalysts, along with the low catalytic activity and poor stability of commercial transition metal catalysts, has prompted researchers to develop catalysts with high conductivity, high stability, high activity, and low cost on a large scale.

[0003] Single-atom catalysts, such as single-atom metal / carbon, single-atom metal / metal oxide, single-atom metal / metal sulfide, and single-atom metal / alloy, have been widely used in electrochemical hydrogen evolution reactions due to their high activity, which can maximize the atomic efficiency of the hydrogen evolution reaction and reduce the amount of catalyst used.

[0004] Single-atom catalysts are typically prepared by introducing a targeted single-atom metal into a substrate to create a precursor, followed by heat treatment to anchor the targeted single-atom metal onto different substrates. To achieve good loading of the single-atom metal and strong interactions between the single-atom metal and the substrate, strategies such as abundant defects, non-uniform atomic doping, selective crystal facet exposure, or rich contact surfaces with the substrate are usually required, which significantly increases the fabrication difficulty. Therefore, simplifying the preparation process of single-atom catalysts and improving the universality of the selection of targeted single-atom metal ions are crucial for expanding the diversity and availability of single-atom materials. However, most reported methods currently suffer from complex fabrication processes, low single-atom metal dispersion, high post-processing temperatures (typically above 700 °C), and environmental unfriendliness, which greatly hinder the practical application of single-atom catalysts. Furthermore, existing methods often require the construction of low-dimensional, porous substrates with abundant grain boundaries to increase single-atom exposure, which places even higher demands on the preparation of single-atom catalysts. For example, the use of porous metal-organic frameworks (MOFs) or covalent organic frameworks (COFs) as precursors to construct single-atom catalysts has recently attracted considerable attention. However, the synthesis and purification of MOFs / COFs, as well as the subsequent metal ion adsorption process, is a very time-consuming process. Other reports have addressed this issue by adding the target metal species beforehand during MOF / COF preparation; however, this may interfere with the framework formation of MOFs / COFs. Furthermore, due to the involvement of harmful organic raw materials, complex synthesis parameters, high-precision pyrolysis temperature control, and the release of organic waste gases during carbonization, this method is considered unsustainable, inefficient, and cumbersome, severely limiting its flexibility and versatility.

[0005] In summary, current single-atom catalysts suffer from problems such as complex preparation, high cost, long preparation time, environmental unfriendliness, poor universality, and poor feasibility for mass production. There is an urgent need to develop a single-atom catalyst preparation method that overcomes these defects. Summary of the Invention

[0006] In view of the current state of the technology, this invention proposes for the first time a method for preparing single-atom-based catalysts using mineral gels. This method is simple, low-cost, time-saving, environmentally friendly, highly versatile, and has excellent feasibility for mass production. The single-atom-dispersed heterostructure catalysts prepared by this method can be used in water electrolysis for hydrogen production, fuel cells, air batteries, etc., and have many advantages such as high catalytic activity, low overpotential, and good stability. They have very good application prospects in the field of energy conversion.

[0007] Specifically, the present invention provides the following technical solution:

[0008] A catalyst is a single-atom dispersed heterostructure catalyst, the catalyst comprising a heterostructure and a metal dispersed in the heterostructure in single-atom form, the heterostructure being a heterostructure composed of several oxides and / or several phosphides of a high-valence metal.

[0009] Specifically, in the single-atom dispersed heterostructure catalyst, the metal dispersed in the heterostructure in the form of single atoms is a catalytically active metal. For example, the catalytically active metal includes at least one of iron, cobalt, nickel, copper, silver, and manganese.

[0010] Specifically, in the single-atom dispersed heterostructure catalyst, the atomic ratio of the metal dispersed in the heterostructure in the form of single atoms is 0.3 at% to 20 at, and the atomic ratio of the remaining heterostructure components is 80 at% to 99.7 at.

[0011] Specifically, in the heterostructure of the above catalyst, the high-valence metal includes at least one of vanadium, molybdenum, tungsten, and manganese.

[0012] Specifically, the heterostructure of the above catalyst simultaneously includes several oxides and / or several phosphides of high-valence metals. For example, the heterostructure is composed of molybdenum dioxide, molybdenum phosphide and molybdenum diphosphide; tungsten oxide, tungsten phosphide and tungsten diphosphide; vanadium oxide and vanadium phosphide; molybdenum oxide and molybdenum phosphide; manganese oxide and manganese phosphide; molybdenum dioxide, molybdenum trioxide and molybdenum phosphide; vanadium pentoxide, vanadium oxide and vanadium phosphide; or manganese dioxide, manganese trioxide and manganese phosphide.

[0013] Specifically, the microstructure of the heterostructure of the above catalyst is a low-dimensional porous nanostructure, such as nanosheets, nanowires, and nanotubes; specifically, it is a two-dimensional porous nanosheet, a one-dimensional porous nanowire, or a one-dimensional porous nanotube.

[0014] Specifically, the catalyst has the same microstructure as the heterostructure.

[0015] The present invention also provides a method for preparing the above-mentioned single-atom dispersed heterostructure catalyst, the method comprising the following steps:

[0016] S1. Mix the first type of metal salt solution and the second type of metal salt solution at room temperature and let stand to obtain a suspension; wherein, the first type of metal is a single-atom dispersed target metal with catalytic activity, and the second type of metal is a high-valence state metal with a heterostructure that is different from the first type of metal and can easily generate several different oxides or phosphides at the same time.

[0017] S2. Centrifuge the suspension to remove excess water to obtain a mineral gel;

[0018] S3. The mineral gel is used as a precursor and then subjected to heat treatment, washing and drying to obtain the single-atom dispersed heterostructure catalyst.

[0019] Specifically, in S1, the concentration of the first type of metal salt solution is 0.1–1 mol / L. -1 .

[0020] Specifically, in S1, the first type of metal salt is a soluble nitrate, sulfate, or chloride salt of a first type of metal.

[0021] Specifically, in S1, the second type of metal salt is an inorganic salt of a high-valence metal, such as phosphomolybdic acid, phosphotungstic acid, phosphovanadic acid, ammonium molybdate, ammonium tungstate, phosphomanganic acid, silicomolybdic acid, and silicotungstic acid.

[0022] Specifically, in S1, the concentration of the second type of metal salt solution is 10–40 g / L. -1 .

[0023] Specifically, in S1, the settling time is 5 to 48 hours.

[0024] Specifically, in S1, the centrifugation speed is 1000-8000 rpm.

[0025] Specifically, the mineral gel in step S2 has a low-dimensional nanostructure. Preferably, the mineral gel has a nanosheet (specifically, a two-dimensional porous nanosheet), nanowire, or nanotube structure. Specifically, the mineral gel is a wrinkled two-dimensional nanosheet cross-linked product, a nanowire cross-linked product, or a nanotube cross-linked product.

[0026] Specifically, in the mineral gel of step S2, both the first type of metal and the second type of metal are monodispersed in the gel structure.

[0027] Specifically, in S3, the heat treatment is either phosphating or oxidation.

[0028] Specifically, in S3, the heat treatment temperature is 450–750°C.

[0029] Specifically, the phosphorus source for the phosphating treatment includes sodium dihydrogen hypophosphite, potassium dihydrogen hypophosphite, or phosphine.

[0030] Specifically, the oxidation process uses one of the following: air or oxygen.

[0031] The present invention also provides the use of the above-mentioned single-atom dispersed heterostructure catalyst, specifically, the catalyst is used for hydrogen production by water electrolysis, fuel cells or air batteries.

[0032] The present invention also provides an electrode comprising the above-described single-atom dispersed heterostructure catalyst.

[0033] The present invention also provides a method for producing hydrogen by electrolysis of water, wherein the above-described single-atom dispersed heterostructure catalyst or the above-described electrode is used.

[0034] The beneficial effects of this invention are:

[0035] 1. This invention provides a single-atom dispersed heterostructure catalyst that can be used in water electrolysis for hydrogen production, fuel cells, air batteries, etc. Specifically, it can catalyze the hydrogen evolution reaction, or serve as an electrode material in fuel cells or air batteries to catalyze electrode reactions. It possesses numerous advantages such as high catalytic activity, low overpotential, and good stability, and has excellent application prospects in the field of energy conversion. For example, the water electrolysis for hydrogen production technology plays a crucial role in achieving the current goal of carbon neutrality.

[0036] The single-atom-dispersed heterostructure catalyst of the present invention possesses unique nanosheet (specifically, two-dimensional porous nanosheets), nanowire or nanotube morphologies, large surface area, and large specific surface area, providing a rapid mass exchange interface for electrochemical reaction processes. Due to its microstructure having a large number of heterostructure interfaces and highly dispersed, highly active single atoms, the optimization of its structure and composition, and the synergistic coupling effect between components, the single-atom-dispersed heterostructure catalyst of the present invention exhibits very good activity and stability. For example, in one specific embodiment, when the catalyst of the present invention is used for hydrogen production by water electrolysis, at a current density of 10 mA cm⁻¹, it exhibits excellent activity and stability. -2 Its overpotential relative to the reversible hydrogen electrode (RHE) is 38.5 mV, while when the current density is increased to 200 mA cm⁻¹ -2 At that time, its overpotential relative to the reversible hydrogen electrode only increased to 109.9 mV, at a current density of 200 mA cm⁻¹. -2 After continuous electrolysis of water for 600 hours, its overpotential only decreased by ~30mV.

[0037] 2. The catalyst of the present invention has better and more stable performance in hydrogen production by water electrolysis than existing commercial precious metal catalysts, thus solving the problem of poor stability of commercial precious metal catalysts.

[0038] 3. The catalyst of the present invention has higher catalytic activity for hydrogen production by water electrolysis than existing commercial transition metal catalysts, thus solving the problem of low valence activity of transition metal catalysts.

[0039] 4. The catalyst obtained by this invention is carbon-free, which can solve the problem of carbon corrosion in many catalytic reactions.

[0040] 5. The catalyst of this invention belongs to the category of single-atom catalysts. Its preparation is simpler, more efficient, more environmentally friendly, and more universal than that of most existing single-atom catalysts. Most importantly, it solves the problem of poor mass production of single-atom catalysts.

[0041] 6. In the preparation method of the catalyst of the present invention, mineral gel is used as a precursor, taking advantage of the highly uniform dispersion of various elements in the mineral gel, and the fact that the metal elements are dispersed at single atoms. In a specific embodiment, phosphating treatment is performed. It has been found that by controlling the temperature of the phosphating treatment, the metal atoms (such as iron atoms) still maintain a single-atom dispersed state. These metal atoms maintain their single-atom dispersion in the single-atom dispersed heterostructure by coordinating with oxygen atoms.

[0042] 7. The single-atom dispersed heterostructure catalyst of the present invention has low production cost. Specifically, it uses inexpensive inorganic salts as raw materials and water as a solvent. The mineral gel can be obtained by mixing, standing, and centrifuging at room temperature. In other words, the inorganic salts used in the method of the present invention are low in cost and widely available, and the production process is simple, requiring only simple solution mixing and heat treatment, which is highly beneficial for large-scale production. In one specific embodiment, the preparation cost of the catalyst of the present invention is approximately RMB 285 per kilogram, while the cost of currently commercially available precious metals is approximately RMB 84,000 per kilogram. A detailed comparison can be found in [reference needed]. Figure 15 Therefore, it can solve the problem of the high price of commercial precious metal catalysts.

[0043] 8. The preparation method of the present invention is fast, simple, safe and feasible. The process of preparing precursor by solution mixing and standing is a low-cost production method that can be applied on a large scale. Attached Figure Description

[0044] The accompanying drawings are included to provide a further understanding of the invention and are incorporated into and constitute a part of this specification. The components in the drawings are not necessarily to scale, but rather to emphasize the principles of the embodiments of the invention. The drawings illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0045] Figure 1 This is a photograph of the mineral gel from Example 1;

[0046] Figure 2 This is a scanning electron microscope image of the mineral gel nanosheets in Example 1 (scale bar is 1 μm) (the text in the electron microscope images has no other meaning except to indicate necessary information such as magnification and length);

[0047] Figure 3 This is a transmission electron microscope image of the mineral gel nanosheets in Example 1 (scale bar is 200 nm);

[0048] Figure 4 This is a high-resolution transmission electron microscope image (scale bar 5 nm) of the mineral gel nanosheets in Example 1.

[0049] Figure 5This is the X-ray diffraction pattern of the single-atom dispersed heterostructure catalyst in Example 1;

[0050] Figure 6 This is a transmission electron microscope image (scale bar 100 nm) of the single-atom dispersed heterostructure catalyst of Example 1.

[0051] Figure 7 This is a high-resolution transmission electron microscope image (scale bar 5 nm) of the single-atom dispersed heterostructure catalyst of Example 1.

[0052] Figure 8 This is an aberration-corrected electron microscopy atomic-level energy spectrum (scale bar 1 nm) of the single-atom dispersed heterostructure catalyst of Example 1.

[0053] Figure 9 The pore size analysis and nitrogen adsorption-desorption curves of the single-atom dispersed heterostructure catalyst in Example 1 are shown.

[0054] Figure 10 This is the X-ray absorption near-edge structure spectrum of the iron K-side of the single-atom dispersed heterostructure catalyst in Example 1;

[0055] Figure 11 It is the extended X-ray absorbing fine structure of the iron K-edge of the single-atom dispersed heterostructure catalyst in Example 1;

[0056] Figure 12 The wavelet transform spectrum of the extended X-ray absorption fine structure of the iron K-edge of the single-atom dispersed heterostructure catalyst in Example 1 is shown.

[0057] Figure 13 The polarization curves are those of the single-atom dispersed heterostructure catalyst in Example 1.

[0058] Figure 14 The single-atom dispersed heterostructure catalyst of Example 1 was tested at 200 mA cm⁻¹. -2 The stability test results are as follows.

[0059] Figure 15 This is a cost comparison of the single-atom dispersed heterostructure catalyst in Example 1 with other noble metal catalysts. Detailed Implementation

[0060] This invention provides several strategies, including: 1) a strategy for synthesizing a single-atom dispersed heterostructure catalyst using a two-dimensional mineral gel as a precursor, specifically, the single-atom dispersed heterostructure catalyst is generated from the mineral gel precursor through simple heat treatment, such as phosphating or oxidation; 2) a heterostructure composed of several oxides and / or several phosphides of a high-valence metal; 3) the mineral gel is formed by self-assembly after simple mixing of two inorganic salt aqueous solutions; 4) in the single-atom dispersed heterostructure, the metal atoms (such as iron atoms) are single-atom dispersed and heterostructured. The structure may be composed of molybdenum dioxide / molybdenum phosphide / molybdenum diphosphide; 5) The single-atom dispersed metal may also be composed of one or more of iron, cobalt, nickel, copper, silver, and manganese, such as iron single atoms, iron-cobalt bimetallic single atoms, nickel-manganese bimetallic single atoms, manganese-cobalt-nickel trimetallic single atoms, iron-cobalt-manganese trimetallic single atoms, iron-cobalt-nickel-manganese tetrametallic single atoms, iron-cobalt-nickel-copper tetrametallic single atoms, etc.; 6) The heterostructure may also be composed of oxides, phosphides, or mixtures thereof of tungsten, vanadium, and manganese, with single atoms dispersed in the heterostructure; etc.

[0061] [Single-atom dispersed heterostructure catalysts]

[0062] As mentioned above, the present invention provides a catalyst, which is a single-atom dispersed heterostructure catalyst. The catalyst includes a heterostructure and a metal dispersed in the heterostructure in the form of single atoms. The heterostructure is a heterostructure composed of several oxides and / or several phosphides of a high-valence metal.

[0063] According to one specific embodiment of the present invention, the metal dispersed in the heterostructure in the form of single atoms in the single-atom dispersed heterostructure catalyst is a catalytically active metal. Specifically, it may be a catalytically active metal in water electrolysis for hydrogen production, a catalytically active metal in a fuel cell, or a catalytically active metal in an air battery. Exemplarily, the catalytically active metal includes at least one selected from iron, cobalt, nickel, copper, silver, and manganese.

[0064] According to a specific embodiment of the present invention, the metal dispersed in the heterostructure in the form of single atoms in the single-atom dispersed heterostructure catalyst is a metal with catalytic activity in water electrolysis for hydrogen production. Exemplarily, the metal with catalytic activity in water electrolysis for hydrogen production can be iron, cobalt, nickel, copper, silver, or manganese, used alone or in combination of any of these. Specifically, it can be at least two of iron, cobalt, nickel, copper, silver, and manganese. Exemplarily, it can be a bimetallic single atom, a trimetallic single atom, a tetrametallic single atom, etc., such as iron-cobalt bimetallic single atom, iron-manganese bimetallic single atom, iron-cobalt-nickel trimetallic single atom, iron-nickel-manganese trimetallic single atom, iron-cobalt-manganese trimetallic single atom, iron-cobalt-nickel-manganese tetrametallic single atom, iron-cobalt-nickel-copper tetrametallic single atom, etc.

[0065] According to a specific embodiment of the present invention, in the single-atom dispersed heterostructure catalyst, the atomic ratio of the metal dispersed in the heterostructure in the form of single atoms is 0.3 at% to 20 at, and the atomic ratio of the remaining heterostructure components is 80 at% to 99.7 at.

[0066] According to a specific embodiment of the present invention, the microstructure of the heterostructure is a low-dimensional porous nanostructure, such as nanosheets, nanowires, nanotubes, etc.; specifically, it is a two-dimensional porous nanosheet, a one-dimensional porous nanowire, or a one-dimensional porous nanotube.

[0067] In this invention, the catalyst has the same microstructure as the heterostructure.

[0068] According to a specific embodiment of the present invention, in the heterostructure, the high-valence metal includes a Group VB metal, a Group VIB metal, or a Group VIIB metal, and can be, for example, at least one of vanadium, molybdenum, tungsten, and manganese.

[0069] According to one specific embodiment of the present invention, the heterostructure simultaneously includes several oxides and / or several phosphides of high-valence metals. Exemplarily, the heterostructure may be composed of molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide; or it may be composed of tungsten oxide, tungsten phosphide, and tungsten diphosphide; vanadium oxide and vanadium phosphide; molybdenum oxide and molybdenum phosphide; manganese oxide and manganese phosphide; molybdenum dioxide, molybdenum trioxide, and molybdenum phosphide; vanadium pentoxide, vanadium oxide, and vanadium phosphide; or manganese dioxide, manganese trioxide, and manganese phosphide.

[0070] In this invention, "several" refers to one, two, or more kinds.

[0071] According to one specific embodiment of the present invention, the single-atom dispersed heterostructure catalyst is prepared using mineral gel as a precursor.

[0072] According to a specific embodiment of the present invention, the single-atom dispersed heterostructure catalyst is a carbon-free catalyst, which is beneficial to solving the problem of carbon corrosion in some catalytic reactions.

[0073] [Mineral Gels, Their Preparation and Applications]

[0074] As mentioned above, the present invention provides a mineral gel, which is a low-dimensional nanostructure, such as nanosheets, nanowires, nanotubes, etc.; specifically, it is a wrinkled two-dimensional nanosheet crosslinking, nanowire crosslinking, or nanotube crosslinking; it includes two types of metals, the first type of metal is a target metal with catalytic activity dispersed as a single atom, and the second type of metal is a high-valence metal that is different from the first type of metal and can easily generate several different oxides or phosphides at the same time.

[0075] According to one specific embodiment of the present invention, the mineral gel is a mineral hydrogel.

[0076] According to one specific embodiment of the present invention, both the first type of metal and the second type of metal are monodispersed in the microstructure network of the gel.

[0077] According to one specific embodiment of the present invention, the first type of metal may be a catalytically active metal in water electrolysis for hydrogen production, a catalytically active metal in a fuel cell, or a catalytically active metal in an air battery. Exemplarily, the first type of metal includes at least one of iron, cobalt, nickel, copper, silver, and manganese. Specifically, it may be a metal dispersed in a heterostructure in the form of a single atom in the aforementioned single-atom dispersed heterostructure catalyst.

[0078] According to one specific embodiment of the present invention, the second type of metal includes group VB metals, group VIB metals or group VIIB metals, and can be, for example, at least one of vanadium, molybdenum, tungsten and manganese.

[0079] According to one specific embodiment of the present invention, the mineral gel is prepared by rapidly and directly mixing aqueous solutions of two inorganic salts and then self-assembling them into gel networks of various morphologies. In this process, both the first and second type of metals are monodispersed within the gel network. After heat treatment, the second type of metal can be transformed into a heterogeneous structure of metal oxides / phosphides / sulfides, while the first type of metal remains monodispersed in the heterogeneous structure in a single-atom state. Specifically, during the heat treatment process, the second type of metal preferentially forms different oxides or phosphides. Due to the strong interaction between oxygen atoms and the atoms of the first type of metal, the first type of metal can maintain a monodisperse state in the heterogeneous structure material derived from the mineral gel.

[0080] This invention presents, for the first time, a mineral gel and reveals it as an ideal candidate material for the synthesis of single-atom catalysts. Furthermore, the strong ionic properties of mineral gels allow for the easy containment of highly dispersed metal ions (such as first-order metals), implying a high degree of tunability of the target single atom. Additionally, these metal ions can be added prior to the gelation process, avoiding the prolonged metal adsorption process of porous precursors. More importantly, the range of metals that can be selected can be expanded to include cheaper mineral metals to construct mineral gels, thereby mitigating the high cost and environmentally unfriendly issues associated with precious metals in the synthesis process. In summary, compared to other common single-atom matrix precursors (such as porous frameworks and carbon), mineral gels demonstrate significant advantages in terms of synthetic routes, environmental friendliness, production efficiency, tunability, raw materials, sustainability, versatility, and cost-effectiveness.

[0081] The present invention also provides a method for preparing the above-mentioned mineral gel, the method comprising the following steps:

[0082] S1. Mix the first type of metal salt solution and the second type of metal salt solution at room temperature and let stand to obtain a suspension; wherein, the first type of metal is a single-atom dispersed target metal with catalytic activity, and the second type of metal is a high-valence state metal with a heterostructure that is different from the first type of metal and can easily generate several different oxides or phosphides at the same time.

[0083] S2. Centrifuge the suspension to remove excess water to obtain the mineral gel.

[0084] According to a specific embodiment of the present invention, in S1, the concentration of the first type of metal salt solution is 0.1–1 mol / L. -1 .

[0085] According to a specific embodiment of the present invention, in S1, the first type of metal salt is an easily soluble nitrate, sulfate, or chloride salt of a first type of metal ion.

[0086] For example, the first type of metal salt can be an iron salt, nickel salt, cobalt salt, or manganese salt, or a mixture of iron salt and other metal salts; specifically, the iron salt can be Fe(NO3)3, Fe(NO3)3·9H2O, FeCl3, or Fe(Cl3)3·6H2O. Specifically, the nickel salt can be NiSO4 or Ni(NO3)2. Specifically, the cobalt salt can be CoCl2 or Co(NO3)2. Specifically, the manganese salt can be MnSO4, Mn(NO3)2, or MnCl2.

[0087] According to a specific embodiment of the present invention, the first type of metal salt solution is a mixed solution of the iron salt and other target metal salts. For example, it can be a mixed solution of inorganic salts such as iron, cobalt, nickel, copper, silver, and manganese. These inorganic salts are water-soluble, such as their soluble nitrates, sulfates, and chlorides. Exemplarily, the concentration of the mixed salt is 0.1–1 mol / L. -1 .

[0088] According to one specific embodiment of the present invention, the molar ratio of the first type of metal salt to the second type of metal salt is 13 to 59.

[0089] According to a specific embodiment of the present invention, in S1, the second type of metal salt is an inorganic salt of a high-valence metal, including inorganic salts of Group VB, Group VIB or Group VIIB metals, such as phosphomolybdic acid, phosphotungstic acid, phosphovanadic acid, ammonium molybdate, ammonium tungstate, phosphomanganic acid, silicomolybdic acid and silicotungstic acid, etc.

[0090] According to a specific embodiment of the present invention, in S1, the concentration of the second type of metal salt solution is 10–40 g / L. -1 .

[0091] According to a specific embodiment of the present invention, in S1, the settling time is 5 to 48 hours.

[0092] According to a specific embodiment of the present invention, in S1, the centrifugal speed is 1000-8000 rpm.

[0093] According to one specific embodiment of the present invention, the method can prepare two-dimensional mineral gel nanosheets using an aqueous solution of pure inorganic salts, without using any organic solvents, and can be carried out at room temperature without heating.

[0094] The present invention also provides the application of the above-mentioned mineral gel for the preparation of the above-mentioned single-atom dispersed heterostructure catalyst.

[0095] [Preparation of Single-Atom Dispersed Heterogeneous Catalysts]

[0096] The present invention also provides a method for preparing the single-atom dispersed heterostructure catalyst, comprising the following steps:

[0097] S1. Mix the first type of metal salt solution and the second type of metal salt solution at room temperature and let stand to obtain a suspension; wherein, the first type of metal is a single-atom dispersed target metal with catalytic activity, and the second type of metal is a high-valence state metal with a heterostructure that is different from the first type of metal and can easily generate several different oxides or phosphides at the same time.

[0098] S2. Centrifuge the suspension to remove excess water to obtain a mineral gel;

[0099] S3. The mineral gel is used as a precursor and then subjected to heat treatment, washing and drying to obtain the single-atom dispersed heterostructure catalyst.

[0100] According to a specific embodiment of the present invention, the specific conditions in steps S1 and S2 are the same as above.

[0101] According to one specific embodiment of the present invention, in S3, the heat treatment is phosphating or oxidation.

[0102] According to one specific embodiment of the present invention, in S3, the heat treatment temperature is 450-750°C.

[0103] According to a specific embodiment of the present invention, S3 specifically includes the following steps:

[0104] a) Take the mineral gel in S2 and mix it evenly with sodium chloride to obtain a mixture of mineral gel and NaCl;

[0105] b) Phosphating treatment: The mixture of mineral gel and NaCl obtained above is placed in a porcelain boat and placed in the lower gas flow position of a tube furnace; the phosphorus source for phosphating treatment is placed in another porcelain boat and placed in the upper gas flow position of a tube furnace, argon gas is introduced into the tube furnace for protection, and after heating for a certain period of time, a mixture of the catalyst of the present invention and sodium chloride is obtained.

[0106] Alternatively, oxidation treatment: place the mixture of the above-obtained mineral gel and NaCl in a porcelain boat and place it in the airflow position of a tube furnace; introduce oxygen or air into the tube furnace and heat for a certain time to obtain a mixture of the catalyst of the present invention and sodium chloride;

[0107] c) The mixture of the catalyst of the present invention and sodium chloride is washed three times with water and then dried in an oven to obtain the catalyst of the present invention.

[0108] According to one specific embodiment of the present invention, the phosphating treatment temperature is 450–750°C.

[0109] According to a specific embodiment of the present invention, the phosphorus source for the phosphating treatment is sodium dihydrogen hypophosphite, potassium dihydrogen hypophosphite, or phosphine.

[0110] According to one specific embodiment of the present invention, the oxidation treatment is performed using one of the following: air, oxygen, etc.

[0111] Applications of single-atom dispersed heterostructure catalysts

[0112] The present invention also provides the use of the above-described single-atom dispersed heterostructure catalyst for hydrogen production by water electrolysis, fuel cells or air batteries.

[0113] Specifically, it is used to catalyze the hydrogen evolution reaction in water electrolysis for hydrogen production.

[0114] Specifically, electrode materials used in fuel cells or air batteries can catalyze electrode reactions.

[0115] The present invention also provides an electrode comprising the above-described single-atom dispersed heterostructure catalyst.

[0116] According to one specific embodiment of the present invention, the electrode further includes a substrate on which the single-atom dispersed heterostructure catalyst is dispersed. Exemplarily, the substrate is carbon paper.

[0117] The present invention also provides a method for producing hydrogen by electrolysis of water, wherein the above-described catalyst or electrode is used.

[0118] Certain exemplary embodiments will now be described to provide a general understanding of the catalysts, methods, and applications disclosed herein. Those skilled in the art will understand that the results specifically described herein and illustrated in the accompanying drawings are non-limiting exemplary embodiments. Features shown or described in connection with one exemplary embodiment may be combined with features of other embodiments. These modifications and variations are intended to be included within the scope of this disclosure. Furthermore, in this disclosure, similar components of various embodiments generally have similar characteristics when they have similar properties and / or serve similar purposes.

[0119] Example 1

[0120] S1 and S2. Preparation of mineral gels

[0121] 0.5 mol L -1 60 mL of Fe(NO3)3·9H2O aqueous solution and 15 g L -1 After mixing 150 mL of phosphomolybdic acid aqueous solution and letting it stand for 30 h, the excess water was removed by centrifugation at 2000 rpm to obtain mineral gel, denoted as FePMoG.

[0122] The above-mentioned settling process does not use any organic solvents and can be carried out at room temperature without heating. Iron ions and phosphomolybdic acid will spontaneously self-assemble to form two-dimensional nanosheets. The resulting nanosheets are wrinkled, have a smooth surface, a thickness of about 50 nm, and a size that can reach the micrometer scale.

[0123] Figure 1 This is a photograph of the mineral gel from Example 1; Figure 2 This is a scanning electron microscope image (scale bar 1 μm) of the mineral gel nanosheets in Example 1; Figure 3 This is a transmission electron microscope image of the mineral gel nanosheets in Example 1 (scale bar is 200 nm); Figure 4 This is a high-resolution transmission electron microscope image (scale bar 5 nm) of the mineral gel nanosheets from Example 1. As shown in the figure, these nanosheets are amorphous, and the elements Fe, Mo, P, and O are highly uniformly dispersed within them.

[0124] S3. Preparation of heterostructure catalysts with single-atom iron dispersion

[0125] Take 65g of FePMoG mineral gel from S2 and mix it evenly with 100g of sodium chloride to obtain a mixture of FePMoG and NaCl.

[0126] The mixture of FePMoG and NaCl obtained above was placed in a ceramic boat and positioned in the lower gas flow position of a tube furnace. 100g of sodium hypophosphite was placed in another ceramic boat as the phosphorus source for phosphating treatment and positioned in the upper gas flow position of a tube furnace. Argon gas was introduced into the tube furnace for protection. After heating at 600℃ for 5h, a mixture of iron single-atom dispersed molybdenum compound heterostructure catalyst and sodium chloride was obtained.

[0127] The mixture was washed three times with water and then dried in an oven to obtain a black, nanosheet-like heterostructure catalyst with single-atom dispersion of iron, denoted as catalyst Fe / SAs@MoO2-MoP-MoP2. The iron in this catalyst is in a single-atom dispersed state, with an atomic percentage of 5 at%, while its heterostructure consists of molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide, with an atomic percentage of 95 at%.

[0128] Figure 5 This is the X-ray diffraction pattern of the catalyst Fe / SAs@MoO2-MoP-MoP2. As can be seen from the figure, the catalyst contains three phases: molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide, and there are no diffraction peaks of any iron compounds. Figure 6 This is a transmission electron microscope image (scale bar 100 nm) of the catalyst Fe / SAs@MoO2-MoP-MoP2. As can be seen from the image, the catalyst maintains the morphology of two-dimensional nanosheets, and these nanosheets are porous. Figure 7 This is a high-resolution transmission electron microscope image (scale bar 5 nm) of the catalyst Fe / SAs@MoO2-MoP-MoP2. As can be seen from the image, there are lattice fringes of the corresponding crystal planes of the three phases: molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide. The heterostructure formed by the contact of these three substances has abundant phase interfaces. Figure 8 The image is a high-resolution spherical aberration transmission electron microscopy (ETEM) spectrum of the catalyst Fe / SAs@MoO2-MoP-MoP2. It can be seen that the iron atoms are dispersed individually, unlike molybdenum which forms a lattice with oxygen and phosphorus atoms.

[0129] Figure 9The images show the pore size analysis and nitrogen adsorption-desorption curves of the catalyst Fe / SAs@MoO2-MoP-MoP2 in Example 1. It can be seen that the catalyst has a high specific surface area and is porous, with the pore size distribution mainly in the range of 2 nm to 16 nm. Figure 10-11 This is the synchrotron radiation absorption spectrum of Fe element in the catalyst Fe / SAs@MoO2-MoP-MoP2, where... Figure 10 This is the X-ray absorption near-edge structure spectrum of the iron K-side in Example 1; Figure 11 It is the extended X-ray absorbing fine structure of the iron K-side in Example 1; Figure 12 This is the wavelet transform spectrum of the extended X-ray absorption fine structure of the iron K-side in Example 1. From Figure 10-12 As can be seen, iron atoms only bond with oxygen atoms, indicating that iron is in a monatomic dispersed state.

[0130] This embodiment also provides a method for preparing an electrode, which includes the following steps:

[0131] (1) Cut the carbon paper into small pieces of 1cm*1cm, then clean it with ethanol using ultrasonic cleaning and dry it in an oven for later use;

[0132] (2) 4 mg of the above catalyst Fe / SAs@MoO2-MoP-MoP2 was ultrasonically dispersed in 400 μL of 0.5 wt% Nafion solution (ethanol:water = 3:1) to form a uniform slurry;

[0133] (3) Coat 67 μL of the slurry from step (2) onto the carbon paper in the 1 cm * 1 cm area of ​​step (1), and dry it to obtain the electrode.

[0134] The above-mentioned electrodes can be used as catalyst electrodes for hydrogen production via water electrolysis. Figure 13-14 It can also be used in fuel cells, air batteries and other fields.

[0135] Example 2

[0136] S1 and S2. Preparation of mineral gels

[0137] 0.1 mol L -1 30 mL of FeCl3 aqueous solution and 0.1 mol L -1 After mixing 30 ml of MnSO4 aqueous solution, add 40 g L -1 150 mL of phosphotungstic acid aqueous solution was allowed to stand for 5 h, and after centrifugation at 8000 rpm to remove excess water, a mineral gel, denoted as Fe-Mn-PWG, was obtained. Its microstructure is nanowire-like, and the nanowires in the mineral gel are cross-linked with each other.

[0138] S3. Preparation of iron-manganese bimetallic single-atom dispersed heterostructure catalysts

[0139] Take 65g of Fe-Mn-PWG mineral gel from step S2 and mix it evenly with 100g of sodium chloride to obtain a mixture of Fe-Mn-PWG and NaCl.

[0140] The mixture of Fe-Mn-PWG and NaCl obtained above was placed in a porcelain boat and positioned in the lower gas flow position of a tube furnace. 100g of potassium dihydrogen phosphate was placed in another porcelain boat as the phosphorus source for phosphating treatment and positioned in the upper gas flow position of a tube furnace. Argon gas was introduced into the tube furnace for protection. After heating at 750℃ for 1h, a mixture of iron-manganese bimetallic single-atom dispersed tungstenide heterostructure catalyst and sodium chloride was obtained.

[0141] The mixture was washed three times with water and then dried in an oven to obtain a nanowire-like iron-manganese bimetallic single-atom dispersed heterostructure catalyst. The iron and manganese in this catalyst were in a single-atom dispersed state, with an atomic percentage of 0.3 at%, while its heterostructure consisted of tungsten oxide, tungsten phosphide, and tungsten diphosphide, with an atomic percentage of 99.7 at%.

[0142] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0143] Example 3

[0144] S1 and S2. Preparation of mineral gels

[0145] 0.6 mol L -1 30 mL of FeCl3 aqueous solution and 20 mol L -1 After mixing 30 mL of Mn(NO3)2 aqueous solution, add 20 g L -1 150 mL of silicotungstic acid aqueous solution was allowed to stand for 12 h. After centrifugation at 1000 rpm to remove excess water, a mineral gel, denoted as Fe-Mn-SiWG, was obtained. Its microstructure is nanowire-like, and the nanowires in the mineral gel are cross-linked.

[0146] S3. Preparation of iron-manganese bimetallic single-atom dispersed heterostructure catalysts

[0147] Take 65g of Fe-Mn-SiWG mineral gel from step S2 and mix it evenly with 100g of sodium chloride to obtain a mixture of Fe-Mn-SiWG and NaCl.

[0148] The mixture of Fe-Mn-SiWG and NaCl obtained above was placed in a porcelain boat and then placed in a tube furnace. Phosphine gas was introduced into the tube furnace, and the mixture was heated at 550°C for 3 hours to obtain a mixture of iron-manganese bimetallic single-atom dispersed tungstenide heterostructure catalyst and sodium chloride.

[0149] The mixture was washed three times with water and then dried in an oven to obtain a nanowire-like iron-manganese bimetallic single-atom dispersed heterostructure catalyst. The iron and manganese in this catalyst were in a single-atom dispersed state, with an atomic percentage of 15 at%, while its heterostructure consisted of tungsten oxide, tungsten phosphide, and tungsten diphosphide, with an atomic percentage of 85 at%.

[0150] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0151] Example 4

[0152] S1 and S2. Preparation of mineral gels

[0153] 1 mol L -1 20 mL of NiSO4 aqueous solution, 1 mol L -1 20 mL of Fe(NO3)3·9H2O aqueous solution and 1 mol L - 1 After mixing 20 ml of MnCl2 aqueous solution, add 10 g L -1 150 mL of phosphovanadic acid aqueous solution was allowed to stand for 10 h. After centrifugation at 3000 rpm to remove excess water, a mineral gel, denoted as Ni-Fe-Mn-PVG, was obtained. Its microstructure is nanotube-like, and the nanotubes in the mineral gel are cross-linked.

[0154] S3. Preparation of nickel-iron-manganese trimetallic single-atom dispersed heterostructure catalysts

[0155] 65g of the Ni-Fe-Mn-PVG mineral gel from step S2 was placed in a porcelain boat and then placed in a tube furnace. Oxygen was introduced into the tube furnace, and the mixture was heated at 450℃ for 5 hours to obtain a single-atom dispersed vanadium compound heterostructure catalyst of nickel, iron, and manganese. After washing three times with water, the catalyst was dried in an oven to obtain a nanotube-shaped single-atom dispersed heterostructure catalyst of nickel, iron, and manganese. The nickel, iron, and manganese in this catalyst are in a single-atom dispersed state, with an atomic percentage of 10 at%, while its heterostructure is composed of vanadium oxide and vanadium phosphide, with an atomic percentage of 90 at%.

[0156] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0157] Example 5

[0158] S1 and S2. Preparation of mineral gels

[0159] 1 mol L -1 NiSO4 aqueous solution, 1 mol L -1 Fe(NO3)3·9H2O aqueous solution, 1 mol L -1 MnCl2 aqueous solution and 1 mol L -1After mixing 20 mL of each CoCl2 aqueous solution, add 20 g L -1 150 mL of ammonium molybdate aqueous solution was allowed to stand for 36 h. After centrifugation at 4000 rpm to remove excess water, a mineral gel, denoted as Ni-Fe-Mn-CoMoOG, was obtained. Its microstructure consisted of wrinkled nanosheets.

[0160] S3. Preparation of nickel-iron-manganese-cobalt tetrametallic single-atom dispersed heterostructure catalysts

[0161] 65g of the Ni-Fe-Mn-CoMoOG mineral gel from step S2 was placed in a porcelain boat and then placed in a tube furnace. Oxygen was introduced into the tube furnace, and the mixture was heated at 600℃ for 3 hours to obtain a single-atom dispersed molybdenum compound heterostructure catalyst of nickel-iron-manganese-cobalt. After washing three times with water, the catalyst was dried in an oven to obtain nanosheet-like single-atom dispersed heterostructure catalyst of nickel-iron-manganese-cobalt. The nickel, iron, manganese, and cobalt in this catalyst are in a single-atom dispersed state, with an atomic percentage of 20 at%, while its heterostructure consists of molybdenum oxide and molybdenum phosphide, with an atomic percentage of 80 at%.

[0162] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0163] Example 6

[0164] S1 and S2. Preparation of mineral gels

[0165] 0.5 mol L -1 60 mL of Ni(NO3)2 aqueous solution and 15 g L -1 After mixing 150 mL of ammonium tungstate aqueous solution and letting it stand for 30 h, the excess water was removed by centrifugation at 5000 rpm to obtain a mineral gel, denoted as Ni-WOG. Its microstructure is nanowire-like, and the nanowires in the mineral gel are cross-linked.

[0166] S3. Preparation of nickel single-atom dispersed heterostructure catalysts

[0167] Following steps similar to those in Example 1, a nanowire-shaped nickel single-atom dispersed heterostructure catalyst was obtained. The nickel was in a single-atom dispersed state, with an atomic percentage of 5 at%, while its heterostructure consisted of tungsten oxide, tungsten phosphide, and tungsten diphosphide, with an atomic percentage of 95 at%.

[0168] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0169] Example 7

[0170] S1 and S2. Preparation of mineral gels

[0171] 0.6 mol L-1 60 mL of Co(NO3)2 aqueous solution and 20 g L -1 After mixing 150 mL of a molybdic acid aqueous solution and letting it stand for 30 h, the excess water was removed by centrifugation at 6000 rpm to obtain a mineral gel, denoted as Co-SiMoG, whose microstructure is a wrinkled nanosheet.

[0172] S3. Preparation of cobalt single-atom dispersed heterostructure catalysts

[0173] Following steps similar to those in Example 1, a nanosheet-like cobalt single-atom dispersed heterostructure catalyst was obtained. The cobalt was dispersed in a single-atom state, with an atomic percentage of 15 at%, while its heterostructure consisted of molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide, with an atomic percentage of 85 at%.

[0174] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0175] Example 8

[0176] S1 and S2. Preparation of mineral gels

[0177] 1 mol L -1 60 mL of Mn(NO3)2 aqueous solution and 10 g L -1 After mixing 150 mL of phosphomanganic acid aqueous solution and letting it stand for 30 h, the excess water was removed by centrifugation at 7000 rpm to obtain a mineral gel, denoted as Mn-PMnG. Its microstructure is nanotube-like, and the nanotubes in the mineral gel are cross-linked.

[0178] S3. Preparation of heterostructured catalysts with single-atom dispersion of manganese

[0179] Following steps similar to those in Example 1, a nanotube-shaped heterostructure catalyst with manganese single-atom dispersion was obtained, wherein the manganese was in a single-atom dispersed state with an atomic percentage of 10 at%, and its heterostructure consisted of manganese dioxide and manganese phosphide with an atomic percentage of 90 at%.

[0180] The method for preparing the electrode in this embodiment is the same as that in Example 1.

[0181] Test Example 1

[0182] Electrocatalytic performance testing of the single-atom dispersed heterostructure catalyst of the present invention

[0183] To demonstrate the electrocatalytic advantages of the single-atom-dispersed heterostructure catalyst of this invention, the HER performance of copper phosphide in 1 mol / L KOH solution was systematically studied using a classic three-electrode system (the electrode prepared in each embodiment of this invention is one of the catalyst electrodes). Figure 13As shown in the linear sweep polarization curves, the single-atom dispersed heterostructure catalyst of this invention exhibits excellent performance in HER: at 10 mA / cm²... 2 At that time, the overpotential relative to the reversible hydrogen electrode (RHE) was 38.5 mV. The catalytic performance test results of the electrodes comprising the single-atom dispersed heterostructure catalyst of the present invention prepared in each embodiment are shown in Table 1.

[0184] Table 1 Comparison of HER performance of the single-atom dispersed heterostructure catalysts of the present invention

[0185]

[0186] Figure 14 The single-atom dispersed heterostructure catalyst of Example 1 was tested at 200 mA cm⁻¹. -2 The stability test results show that the catalyst can operate stably for 600 hours with a voltage drop of less than 30mV.

[0187] Figure 15 This is a cost comparison of the single-atom dispersed heterostructure catalyst of Example 1 with other precious metal catalysts. It can be seen that the preparation cost of the catalyst of this invention is less than USD 50 per kilogram, while the cost of currently commercially available precious metal catalysts is over USD 10,000 per kilogram. This indicates that the catalyst of this invention can solve the problem of the high price of commercially available precious metal catalysts and is a product with great application potential.

[0188] The foregoing description of the present invention is provided for illustrative purposes. It is not intended to be exhaustive or to limit the invention to the precise forms disclosed. Many modifications and variations will be apparent to those skilled in the art.

[0189] These embodiments were chosen and described in order to best explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the various embodiments of the invention and the various modifications suitable for the particular intended use.

Claims

1. A method for preparing a single-atom dispersed heterostructure catalyst, characterized in that, The catalyst comprises a heterostructure and a metal dispersed in the heterostructure in the form of single atoms, wherein the heterostructure is a heterostructure composed of several oxides and / or several phosphides of a high-valence metal. The method includes the following steps: S1. Mix the aqueous solutions of the first type of metal salt and the second type of metal salt at room temperature and let stand to obtain a suspension; wherein, the first type of metal is a single-atom dispersed target metal with catalytic activity, and the second type of metal is a high-valence metal with a heterostructure that is different from the first type of metal and can easily generate several different oxides or phosphides at the same time. The first type of metal salt is an iron salt, nickel salt, cobalt salt, or manganese salt, or a mixture of iron salt and other metal salts; The iron salt is Fe(NO3)3, Fe(NO3)3·9H2O, FeCl3 or Fe(Cl3)3·6H2O; the nickel salt is NiSO4 or Ni(NO3)2; the cobalt salt is CoCl2 or Co(NO3)2; the manganese salt is MnSO4, Mn(NO3)2 or MnCl2; The mixture of iron salt and other metal salts is a mixture of the above-mentioned iron salt with cobalt salt, nickel salt, or manganese salt; The second type of metal salt is at least one of phosphomolybdic acid, phosphotungstic acid, phosphovanadic acid, ammonium molybdate, ammonium tungstate, phosmanganic acid, silimolybdic acid, and silicotungstic acid; The molar ratio of the first type of metal salt to the second type of metal salt is 13 to 59; S2. Centrifuge the suspension to remove excess water to obtain a mineral gel, which is a gel with a low-dimensional nanostructure. S3. The mineral gel is used as a precursor and then subjected to heat treatment, washing and drying to obtain the single-atom dispersed heterostructure catalyst. In S1, the concentration of the first type of metal salt solution is 0.1~1 mol L. -1 ; In S1, the concentration of the second type of metal salt solution is 10~40 g / L. -1 ; In S3, the heat treatment is either phosphating or oxidation. In S3, the heat treatment temperature is 450~750 ℃.

2. The method according to claim 1, characterized in that, In S1, the settling time is 5~48h; And / or, in S1, the centrifugation speed is 1000~8000 rpm.

3. The method according to claim 1, characterized in that, The mineral gel has a nanosheet, nanowire, or nanotube structure; And / or, in the mineral gel of step S2, both the first type of metal and the second type of metal are monodispersed in the gel structure.

4. The method according to claim 3, characterized in that, Mineral gels are cross-linked materials of two-dimensional nanosheets, nanowires, or nanotubes with a wrinkled appearance.

5. The method according to claim 1, characterized in that, The phosphorus source for the phosphating treatment is sodium dihydrogen hypophosphite, potassium dihydrogen hypophosphite, or phosphine. And / or, the oxidation treatment is performed using one of the following: air or oxygen.

6. A single-atom dispersed heterostructure catalyst, which is prepared by the method according to any one of claims 1-5.

7. The single-atom dispersed heterostructure catalyst according to claim 6, characterized in that, In the single-atom dispersed heterostructure catalyst, the metal dispersed in the heterostructure in the form of single atoms is a catalytically active metal, and the catalytically active metal includes at least one of iron, cobalt, nickel, copper, silver and manganese. And / or, in the single-atom dispersed heterostructure catalyst, the atomic ratio of the metal dispersed in the heterostructure in single-atom form is 0.3 at% to 20 at%, and the atomic ratio of the remaining heterostructure components is 80 at% to 99.7 at%. And / or, in the heterostructure, the high-valence metal includes at least one of vanadium, molybdenum, tungsten, and manganese; And / or, the heterostructure simultaneously includes several oxides and / or several phosphides of high-valence metals.

8. The single-atom dispersed heterostructure catalyst according to claim 7, characterized in that, The heterostructure is composed of molybdenum dioxide, molybdenum phosphide, and molybdenum diphosphide; tungsten oxide, tungsten phosphide, and tungsten diphosphide; vanadium oxide and vanadium phosphide; molybdenum oxide and molybdenum phosphide; manganese oxide and manganese phosphide; molybdenum dioxide, molybdenum trioxide, and molybdenum phosphide; vanadium pentoxide, vanadium oxide, and vanadium phosphide; or manganese dioxide, manganese trioxide, and manganese phosphide.

9. The single-atom dispersed heterostructure catalyst according to claim 6, characterized in that, The microstructure of the heterostructure is a low-dimensional porous nanostructure. The catalyst has the same microstructure as the heterostructure.

10. The single-atom dispersed heterostructure catalyst according to claim 9, characterized in that, The microstructure of the heterostructure is a nanosheet, nanowire, or nanotube.

11. The single-atom dispersed heterostructure catalyst according to claim 10, characterized in that, The microstructure of the heterostructure is a two-dimensional porous nanosheet, a one-dimensional porous nanowire, or a one-dimensional porous nanotube.

12. Use of the single-atom dispersed heterostructure catalyst according to any one of claims 6-11, characterized in that, The catalyst is used for hydrogen production by water electrolysis, fuel cells, or air batteries.

13. An electrode, characterized in that, The electrode comprises the single-atom dispersed heterostructure catalyst according to any one of claims 6-11.

14. A method for producing hydrogen by electrolysis of water, wherein a single-atom dispersed heterostructure catalyst as described in any one of claims 6-11 or an electrode as described in claim 13 is used.

Citation Information

Patent Citations

  • Monatomic Pt-loaded tungsten oxide single-layer nanosheet catalyst with ultrahigh catalytic activity as well as preparation method and application thereof

    CN111111658A

  • Manganese-doped transition metal atom metal phosphide catalyst, preparation method and application thereof in hydrogen production by water electrolysis

    CN112121829A

  • Metal phosphide-loaded monatomic catalyst, preparation method thereof and application of metal phosphide-loaded monatomic catalyst as hydrogen evolution reaction electrocatalyst

    CN113249739A

  • Method for preparing superfine cerium dioxide supported metal monatomic catalyst from cluster-based framework material

    CN114293223A

  • Transition metal-based heterostructure electrolyzed water catalyst as well as preparation method and application thereof

    CN115029710A